The natural hybrid between Aloe claviflora and A. ferox (Asphodelaceae [subfam. Asphodeloideae] tr. Aloeae) described as A. ×bornmanii - Smith, Gideon F.; Klopper, Ronell R. (Phytotaxa, 2025)
Aloe ×bornmanii (Asphodelaceae [subfam. Asphodeloideae] tr. Aloeae), the hybrid between A. claviflora and A. ferox, is described from South Africa’s Groot Karoo. Aloe claviflora flowers predominantly in late-winter to spring and A. ferox in mid- to late-winter. In places where the natural distribution ranges of the two species overlap and where early-flowering A. claviflora and late-flowering A. ferox plants co-occur, the hybrid between the two species is often encountered.